Upstream pharmaceutical supply chains of 10 high-use pharmaceuticals in the Netherlands: a cohort study - Aukje K Mantel-Teeuwisse; Hubert G M Leufkens; Peter A G M De Smet; Doerine J Postma; Kim Notenboom (BMJ Open)
Objectives To assess the upstream pharmaceutical supply chains of 10 high-use pharmaceuticals to detect vulnerabilities that may increase the risk of medicine shortages.Design Cohort study.Setting Dutch outpatient setting in 2022.Participants A total of 407 authorised medicinal products for 10 pharmaceutical substances with the largest number of outpatients.Main outcome measures The diversity of active pharmaceutical ingredient (API) and finished pharmaceutical product (FPP) manufacturers, their geographic locations and the interdependencies between these manufacturers and marketing authorisation holders (MAHs).Results For the 407 authorised medicinal products, 50 of the 90 API manufacturing sites were in Asia, and 38 were in Europe. For five pharmaceutical substances, most of the API sites were located outside Europe. Of the 128 FPP manufacturing sites, 94 were in Europe and 31 in Asia. For all 10 substances, at least 47% of FPP sites were located in Europe. API manufacturing for 122 of the 407 products (30%) was entirely performed outside Europe, and FPP manufacturing for 66 of the 407 products (16%). For four substances, more than half of the products depended on API manufacturing outside Europe. The number of distinct API and FPP manufacturing sites per substance was at least four. For amoxicillin, 16 of the 32 products (50%) entirely depended on one and the same API site. For omeprazole, 39 of the 85 products (46%) entirely depended on one and the same FPP site. MAHs applied dual sourcing for API and FPP manufacturing for 61 (15%) of the authorised medicinal products. For three pharmaceutical substances, none of the authorised medicinal products listed at least two API and FPP manufacturing sites.Conclusion Our study of the supply chains of high-use pharmaceutical substances indicates the need for a granular assessment of the interdependencies between MAHs, API and FPP manufacturers to identify upstream supply chain vulnerabilities.